Radula multiflora var. reflexilobula is a synonym of R. decurrens (Radulaceae, Marchantiophyta) - Promma, Chatchaba; Chantanaorrapint, Sahut (Phytotaxa, 2014)
Radula Dumortier (1822: 112) is one of the largest genera of the liverworts with about 200 currently accepted species (Frey & Stech 2009), but some of them are poorly known and their status is still unclear. Radula javanica Gottsche (in Gottsche et al. 1844: 257) is one of the oldest names of Radula which is widespread in the tropical and subtropical Asia, the Pacific Islands and Australasia (Yamada 1979, Renner 2014). So (2006) reduced a highly variable species R. multiflora Gottsche ex Schiffn. (in Engler 1889: 20) to R. javanica Gottsche. However, Renner (2014) suggested that R. multiflora might be different from R. javanica but similar to R. reflexa Nees & Mont. (in Montagne 1843: 255).